1979
DOI: 10.1093/brain/102.3.461
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Stance in Late Cortical Cerebellar Atrophy of the Anterior Lobe and Other Forms of Cerebellar Ataxia

Abstract: (1) Methods have been developed to measure, analyse and document postural sway. The main parameters studied were: average sway amplitude; length of the sway path per unit time; sway direction and sway position histograms; and the frequency spectra of the antero-posterior and lateral sway components. (2) Postural ataxia was quantitatively studied in three groups of patients with cerebellar lesions: (a) late atrophy of the anterior lobe, (b) tumours of the cerebellar hemisphere and (c) tumours within the vestibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
1
3

Year Published

1982
1982
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(117 citation statements)
references
References 0 publications
9
104
1
3
Order By: Relevance
“…The stabilographic study has been reported to contribute to the diagnoses of cerebellar ataxia. 15,16 Recent studies suggest that stabilometry are not always suitable to specify the anatomical region of the responsible focus; however, it can detect subtle vestibulospinal dysfunction. [17][18][19] The mean values of LNG, ENV-AREA, and REC-AREA in EC sessions of the migraine group were significantly greater than in controls, however, the degree of abnormality of stabilometric parameters were smaller than the results of ataxic patients in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The stabilographic study has been reported to contribute to the diagnoses of cerebellar ataxia. 15,16 Recent studies suggest that stabilometry are not always suitable to specify the anatomical region of the responsible focus; however, it can detect subtle vestibulospinal dysfunction. [17][18][19] The mean values of LNG, ENV-AREA, and REC-AREA in EC sessions of the migraine group were significantly greater than in controls, however, the degree of abnormality of stabilometric parameters were smaller than the results of ataxic patients in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Increased power at high frequencies is indicative of instability in adults (Mauritz et al 1979), as is excessive sway in the mediolateral direction (Maki et al 1994, Mitchell et al 1995. While boys had shown age-related reductions in total power, their mean and median power frequency values were consistently lower than girls at 9 to 10 years of age.…”
Section: Years Standing With Eyes Open (Eo) and Eyes Closed (Ec)mentioning
confidence: 98%
“…Frequency analysis of COP has previously been used to measure the development of, or to determine any abnormalities in, the control systems when standing (Mauritz et al 1979, Riach and Hayes 1987, Portfors-Yeomans and Riach 1995, Wolff et al 1998. It has been suggested that increased power at the low end of the frequency spectrum (<0.8Hz) may reflect 'qualitative differences' in vestibular function (Riach and Hayes 1987).…”
Section: Years Standing With Eyes Open (Eo) and Eyes Closed (Ec)mentioning
confidence: 99%
“…Sum of the root 20) . Frequency analysis could be useful in understanding the mechanism of neurotoxicity of occupational and environmental factors, as many clinical studies [31][32][33][34][35][36] have suggested that disorders of the vestibular, spinocerebellar afferent, and cerebellar systems are related to the following changes in specific frequency domains and directions of postural sway.…”
Section: Computerized Static Posturographymentioning
confidence: 99%